Foreign body (toothpick) causing epiglottitis. Issue 2 (2nd April 2020) - Garg, Gunjan; Sawhney, Harpreet; Gandhi, Darshan; Bhatt, Neeraj; Rosovsky, Mark
Abstract: A 25-year-old otherwise healthy woman presented to the hospital with sore throat and dysphagia for 5 days. On her computed tomography images, thickening and edema of the right aryepiglottic fold was noted, associated with an impacted foreign body.